Fossil and Renewable Energy Stock Indices: Connectedness and the COP Meetings - Guglielmo Maria Caporale; Nicola Spagnolo; Awon Almajali (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates static and dynamic connectedness between the first and second moments of fossil and renewable energy stock indices in the last decade at the daily frequency. For this purpose the Diebold and Yilmaz (2014) methodology is applied; in addition, endogenous break tests are carried out and sub-sample estimates are also obtained. The results suggest that renewable energy stock indices play a significant role in terms of connectdness; moreover, the two detected breaks indicate that both the unsuccessful COP17 held in Durban in 2011 and the anticipation of decisive action at the COP26 in Glasgow affected the degree of connectedness. The finding that spillovers are stronger during periods characterised by more effective climate change policies confirms the crucial importance of policy intervention and support for renewable energy to tackle climate change.
Keywords: C32; G15; Q40; 330; COP; fossil and renewable energy; VAR; connectedness